KORELASI DINAMIS EMAS DAN SAHAM SYARIAH SEBAGAI LINDUNG NILAI DAN SAFE HAVEN PADA INVESTASI DI INDONESIA - Nanda Anisa Billah; Deny Dwi Hartomo (Magister Manajemen Fakultas Ekonomi dan Bisnis UNS, 2018)
This study examines the dynamic correlation between gold and sharia stock as a hedge and safe haven in Indonesian financial markets. Researchers used the A-DCC GARCH Model of daily closing price of gold and sharia stock in JII (Jakarta Islamic Index) for the period of 2007 to 2016. The purpose of this study is to analyze the investment choices that should be done by investors whether gold or sharia or gold and sharia stock equity investments are simultaneously combined to protect financial assets primarily in Indonesia's financial markets. In A-DCC the gold model produces a negative correlation especially during periods of crisis indicating that gold can significantly perform its role as a hedge and a safe place for other assets. The researchers also tested empirically for an effective diversification and hedging portfolio for gold and stock combinations. The findings suggest investors should diversify their portfolio by adding gold. Combining gold and stocks together can be a strong hedge and reduce the risk level for investment in Indonesia. Keywords : Hedging, safe haven, gold, index of islam jakarta, syariah stock